Advanced stability criteria for linear systems with time-varying delays. Issue 1 (January 2018) - Park, M.J.; Kwon, O.M.; Ryu, J.H.
Abstract: This paper investigates a stability problem for linear systems with time-varying delays. By constructing suitable augmented Lyapunov–Krasovskii functionals, improved stability criteria under various conditions of time-varying delays are derived within the framework of linear matrix inequalities (LMIs). Moreover, to reduce the computational burden caused by the non-convex term including h 2 ( t ), how to deal with it is applied by estimating it to the convex term including h ( t ). Finally, three illustrative examples are given to show the effectiveness of the proposed criteria.